2018
DOI: 10.1242/dev.161208
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide strategies identify downstream target genes of chick connective tissue-associated transcription factors

Abstract: Connective tissues support organs and play crucial roles in development, homeostasis and fibrosis, yet our understanding of their formation is still limited. To gain insight into the molecular mechanisms of connective tissue specification, we selected five zinc-finger transcription factors - OSR1, OSR2, EGR1, KLF2 and KLF4 - based on their expression patterns and/or known involvement in connective tissue subtype differentiation. RNA-seq and ChIP-seq profiling of chick limb micromass cultures revealed a set of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 91 publications
3
29
0
Order By: Relevance
“…While we concentrated in this study on the attachment site, it is most likely that KLF2/4 play a role also in other musculoskeletal tissues such as the skeleton, tendon and muscle. This possibility is supported by previous studies, where KLF2/4 were shown to be expressed in osteoblasts, chondrocytes, tenocytes and muscle connective tissues [48,49].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…While we concentrated in this study on the attachment site, it is most likely that KLF2/4 play a role also in other musculoskeletal tissues such as the skeleton, tendon and muscle. This possibility is supported by previous studies, where KLF2/4 were shown to be expressed in osteoblasts, chondrocytes, tenocytes and muscle connective tissues [48,49].…”
Section: Discussionsupporting
confidence: 80%
“…This phenotype was more severe than what was observed in embryos that lost only KLF2 or KLF4 [25]. Furthermore, Orgeur et al (2018) identified 313 target genes shared between KLF2 and KLf4, suggesting that they overlap in regulating gene expression.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…OSR1 overexpression suppressed integrin signaling pathway which is involved in cell-cell adhesion and communication. 13 As a critical mediator that connects integrin and the downstream signaling molecules, FAK can be activated by integrin phosphorylation and subsequently activates downstream PI3K/ AKT pathway and MAPK pathway. [14][15][16][17][18][19][20][21] To validate whether OSR1 exerts anti-cancer effects via FAK in COAD, we detected the activation of FAK based on p-FAK level.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that OSR1 suppressed integrin signaling and regulated cell communication and adhesion. 13 Therefore, we detected FAK related signaling pathways in COAD. Western blot analysis demonstrated that OSR1 overexpression significantly decreased the levels of p-FAK, p-p-38, p-ERK1/2, and p-AKT (Ser473), while the levels of total FAK, total p38, total ERK1/2, and total AKT were unaffected.…”
Section: Osr1 Inhibits Akt and Mapk Pathways In Coad Cellsmentioning
confidence: 99%